Psychological interventions for sexual fantasies and implications for sexual violence: A systematic review. (November 2020) - Allen, Andrew; Katsikitis, Mary; Millear, Prudence; McKillop, Nadine
Abstract: Background: Sexual fantasies are a common aspect of human experience and a prominent consideration in the conceptualisation and treatment of harmful sexual behaviour. Yet, little is known about the evidence that supports the use of psychological interventions for sexual fantasies or how such interventions may modify the multifaceted nature of sexual fantasies. The purpose of this systematic review was to examine the existing literature regarding psychological interventions for sexual fantasies in adult forensic and non-forensic populations to provide a synthesis and evaluation of relevant research. Method: A comprehensive search of six electronic databases was undertaken to identify literature regarding psychological interventions for sexual fantasies. Reference lists of articles were also hand searched and contact was made with authors in the field to identify additional works. A total of ten studies were included in the review. Results: From the ten studies, psychological interventions encompassed group-based therapy (e.g., CBT, psychodynamic), concurrent techniques (e.g., covert sensitisation, orgasmic reconditioning, aversive therapy), and individual techniques (e.g., imagery-competitive tasks, in vivo aversive behaviour therapy). The data synthesis indicated a range of differences between studies, warranting caution in interpreting intervention effectiveness and consideration of multiple confounding factors (e.g., population, sample size, methodology, measurement). Conclusion: The evidence tentatively supports the use of group-based therapy in forensic populations as a result of greater research in this area. There are individual psychological interventions that may be beneficial for sexual fantasies in the context of harmful sexual behaviour but more research is required to support their efficacy. Highlights: The evidence of psychological interventions for sexual fantasies across forensic and non-forensic settings was reviewed. The evidence remains limited due to the heterogeneity of available research, study methodologies, and examined populations. Research is required to gauge the multifaceted nature of sexual fantasies targeted by psychological interventions for sexual offending.